A systematic review of the characteristics of data assessment tools to measure medical doctors' work-related quality of life - Miyuki Ezura; Katsuhiko Sawada; Yusuke Takushima; Ataru Igarashi; Lida Teng (Taylor & Francis Group, 2023)
ABSTRACTPurpose: Remarkable progress in healthcare technology has recently been made alongside changes in concepts related to drugs and medical devices. It is speculated that this progress benefits not only patients but also healthcare professionals, such as medical doctors. We performed a systematic review of the characteristics of current data assessment tools to measure medical doctors' work-related quality of life (QOL).Methods: A literature search was conducted through PubMed and Ichushi-Web in 2020. The related search terms used were 'medical doctor,' 'quality of work life,' and 'questionnaire/interview.' Two reviewers independently screened the studies, and the characteristics of the QOL assessment tools used in the identified studies were qualitatively reviewed and summarized.Results: In total, 5,443 and 760 articles were retrieved from PubMed and Ichushi-Web, respectively, of which 82 studies were included in this review. Sixty-five (79%) studies used structured questionnaires, and 17 (21%) studies used semistructured questionnaires. In terms of the study purpose, the identified studies mainly included four: mental health, the work or labor situation, satisfaction, and QOL. Components used to measure work-related QOL included satisfaction, burnout, QOL, the work environment, stress, mental health, work-life balance, and others. None of the studies used an originally developed QOL questionnaire to assess the work-related benefits of medical doctors.Conclusion: This systematic review found that there is a lack of studies directly assessing the work-related QOL of medical doctors and a lack of effective data collection tools to assess all work-related QOL components.